آدم (عليه السلام): لا مكان الاهباط، بل حكمته = Adam’s (peace be upon him) footprint: not the place of descent, but its wisdom - Nasr, Ahmad Abdalrahim; Gasmelsid, Saadeldin Mansour (Red Sea Basin Research and Studies Center, Sudan, 2025)
This study argues against the view that the foot-print on the top of a mountain in the island of Sarandib (formerly Ceylon, and present-day Sri Lanka) is attributed to Adam(peace be upon him) by pointing out that the hadith attributed to the Prophet and the views of some of his companions about the place of Adam’s (peace be upon him) descent are either weak, contradictory or influenced by Hebrews’ traditions or ancient Chinese civilization. It also shows that the indigenous people of Sri Lanka , Buddhists, Hindus, and Christians claim also that the footprint is god Samana’s , Buddha ,Vishnu, Siva, Saint Thomas, or an eunuch of a Queen’s ( Candace ) of Nabtah kingdom respectively . The study argues that a foot-print of a prophet , god, saint, hero or an animal that he used to mount, on a top on a mountain or a rock is a common folkloric motif that allegedly proves the truth of the legends about it. In addition, the Qur’an speaks about the wisdom of descent, not its place.